Heat-labile enterotoxin of Escherichia coli promotes intestinal colonization of Salmonella enterica. (December 2015) - Verbrugghe, Elin; Van Parys, Alexander; Leyman, Bregje; Boyen, Filip; Arnouts, Sven; Lundberg, Urban; Ducatelle, Richard; Van den Broeck, Wim; Yekta, Maryam Atef; Cox, Eric; Haesebrouck, Freddy; Pasmans, Frank
Highlights: LT produced by ETEC promotes intestinal colonization of Salmonella Typhimurium. LT does not directly affect interactions of Salmonella with enterocytes. LT alters the continuity of the epithelial mucin layer. LT alters mucin expression by goblet cells. Abstract: Enterotoxigenic Escherichia coli (ETEC) is an important cause of infantile and travellers' diarrhoea, which poses a serious health burden, especially in developing countries. In addition, ETEC bacteria are a major cause of illness and death in neonatal and recently weaned pigs. The production of a heat-labile enterotoxin (LT) promotes the colonization and pathogenicity of ETEC and may exacerbate co-infections with other enteric pathogens such as Salmonella enterica . We showed that the intraintestinal presence of LT dramatically increased the intestinal Salmonella Typhimurium load in experimentally inoculated pigs. This could not be explained by direct alteration of the invasion or survival capacity of Salmonella in enterocytes, in vitro . However, we demonstrated that LT affects the enteric mucus layer composition in a mucus-secreting goblet cell line by significantly decreasing the expression of mucin 4. The current results show that LT alters the intestinal mucus composition and aggravates a Salmonella Typhimurium infection, which may result in the exacerbation of the diarrhoeal illness.